PROGRAM EVALUATION OF READING PLUS : STUDY OF THE IMPACT ON READING ACHIEVEMENT FOR NINTH-GRADE STUDENTS IN MOORE COUNTY SCHOOLS - County, Joel M. (East Carolina University, 2015)
The following is a program evaluation of the Reading Plus program in Moore County Schools from southern North Carolina and its impact on reading achievement for ninth-grade students. Reading Plus is a valuable asset that may be utilized to increase student ability to read. The Reading Plus program increases the degree of phonemic awareness, phonics, fluency, reading stamina, comprehension, character recognition and recall, vocabulary acquisition skills, and Lexile levels of students when the program is implemented with fidelity. The results of this study show that students who spent sufficient time on task, with each component of the program, demonstrated growth in all the areas mentioned above. Teachers who implemented this pilot were overwhelmingly pleased with the student outcomes and the program itself. The outcomes of this program evaluation were so impressive that the Reading Plus program is now being implemented at Riverside High School in Durham Public Schools, located in central North Carolina.
Keywords: Reading remediation; Reading--Remedial teaching--North Carolina--Moore County--Aids and devices--Evaluation; Reading (Middle school)--North Carolina--Moore County; Moore County Schools; Reading plus (Winooski, Vt.)